PEMBERDAYAAN PETANI OLEH ORMAS MENURUT TINGKAT PARTISIPASI DI KABUPATEN BANDUNG - Utan Sahiro Ritonga (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Currently empowerment program has become a mission of religion community organizations in Indonesia. As non government element and non business oriented organization it is necessary to know performance of empowerment programs based of farmer participation level. With a quantitative descriptive research approach using questionnaire in collecting of data survey were obtained 75 respondents taken with purposive sampling technique in Bandung Regency. Based results of cumulative calculations, known that farmer participation in empowerment program into middle category for socialization activity and low category for implementation activity of programs. Chi square pearson’s and gamma test known were farmer age has positively correlated to participation in activity of program implementing, meanwhile education, income, and farmer status has negatively correlated to farmer participation for avtivity implementation of programs. Farmer characteristic has correlated to participation required by ormas before conducting of empowerment program as a strategic to success of program likely participatory.